2016
DOI: 10.1016/j.cardfail.2016.06.343
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and LVADs, Is There an Income Disparity?

Abstract: an abnormal DSE can reliably predict the development of CAV or risk of death on follow up. Hypothesis: We hypothesize that among patients with cardiac transplantation, abnormal DSEs are not predictive of CAV or survival upon follow up. Methods: We retrospectively examined all patients who received a heart transplant at our institution between 2004-2013 (n = 192) if they had at least one DSE (6, 18 or 30 months posttransplant) followed by a coronary angiogram (annually) and excluded those with no DSEs (n = 62)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Historically, minorities were found to be more likely to be affected by limited preventative care, lack of counseling about therapeutic options, and experience delays in transplantation referrals when indicated. 2,3,9,10 With targeted and concentrated efforts, disparities in the use of and access to advanced therapies such as mechanical circulatory support have been noted to be improving or alleviated. [6][7][8] However, although several studies have examined outcomes after LVAD implantation and observed no significant survival difference based on race, 4,5,9,11 rigorous evaluation of racial disparities in patients successfully bridged to transplantation with an LVAD continues to be lacking.…”
Section: Commentmentioning
confidence: 99%
“…Historically, minorities were found to be more likely to be affected by limited preventative care, lack of counseling about therapeutic options, and experience delays in transplantation referrals when indicated. 2,3,9,10 With targeted and concentrated efforts, disparities in the use of and access to advanced therapies such as mechanical circulatory support have been noted to be improving or alleviated. [6][7][8] However, although several studies have examined outcomes after LVAD implantation and observed no significant survival difference based on race, 4,5,9,11 rigorous evaluation of racial disparities in patients successfully bridged to transplantation with an LVAD continues to be lacking.…”
Section: Commentmentioning
confidence: 99%